Bad Arguments and Objectively Bad Arguments - Hoffmann, Michael H.G.; Catrambone, Richard (Informal Logic, 2023)
Many have argued that it is impossible to determine criteria to identify good arguments. In this contribution, we argue that it is at least possible to identify features of objectively bad arguments. Going beyond Blair and Johnson’s ARS criteria, which state that reasons must be acceptable, relevant, and sufficient, we develop a list of eight criteria with instructions for how to apply them to assess arguments. We conclude by presenting data from two empirical studies that show how frequently students violate these criteria in lab conditions and “in the wild.”